The Effect of STEM Approach in Problem-based Learning for Increasing Students' Problem-solving Ability in the Topic of Environmental Pollution - Parno, ‎; Pratiwi, Novida; Putri, Faizza Amaliah; Ali, Marlina (KnE Social Sciences, 2024)
Environmental pollution is a manifestation of the interaction between living things and their environment. However, students still have low problem-solving ability (PSA) in this topic. Meanwhile, STEM approach implementation in problem-based learning (PBL-STEM) to grow students’ PSA is still rarely used. This study aims to improve students’ PSA by implementing STEM approach in PBL on the environmental pollution topic. This quasi-experimental research uses a pre- and post-test design. This study was done on a group of 64 7th grade students, who were equally divided into experimental class (PBL-STEM) and comparison class (PBL) In completing the worksheet during learning, the experimental class students were required to be more active in terms of thinking, than the comparison class students. This study uses the environmental pollution problem-solving ability test instrument, which consists of 13 essay items with a Cronbach alpha reliability of 0.785. Pre- and post-test data were analyzed using independent t-test, N-gain, and d-effect size. The results showed that students who studied through PBL with the STEM approach had significantly better PSA than students who studied through PBL. Also, students in the experimental class had a larger N-gain increase compared to the comparison class, both in total topics and subtopics of environmental pollution. Even in the subtopic of noise pollution, the PSA of the subjects in experimental class improved one level higher than the subjects in comparison class. Both classes had the same increase in succession from large to small, namely, water, soil, air, and noise pollution. The practical implementation of the research resulted in a d-effect of 0.782 medium category. Therefore, the STEM approach in PBL affects increasing students’ PSA on the topic of environmental pollution. In future research, it is recommended to add “Religious” and “Art” aspects of STEM, and be equipped with formative assessment in the whole learning process. Keywords: STEM approach, problem-based learning, problem-solving ability, environmental pollution